Cost effectiveness of dietitian‐led nutrition therapy for people with type 2 diabetes mellitus: a scoping review. Issue 1 (14th October 2020) - Siopis, G.; Wang, L.; Colagiuri, S.; Allman‐Farinelli, M.
Abstract: Background: The management of diabetes costs in excess of $1.3 trillion per annum worldwide. Diet is central to the management of type 2 diabetes. It is not known whether dietetic intervention is cost effective. This scoping review aimed to map the existing literature concerning the cost effectiveness of medical nutrition therapy provided by dietitians for people with type 2 diabetes. Methods: Thirteen scientific databases, including MEDLINE, EMBASE and CINAHL, as well as multiple official websites, were searched to source peer‐reviewed articles, reports, guidelines, dissertations and other grey literature published from 2008 to present. Eligible articles had to have assessed and reported the cost effectiveness of dietetic intervention for adults with type 2 diabetes in developed countries. Experimental, quasi‐experimental, observational and qualitative studies were considered. Results: Of 2387 abstracts assessed for eligibility, four studies combining 22 765 adults with type 2 diabetes were included. Dietetic intervention was shown to be cost‐effective in terms of diabetes‐related healthcare costs and hospital charges, at the same time as also reducing the risk of cumulative days at work lost to less than half and the risk of disability 'sick' days at work to less than one‐seventh. Conclusions: The findings highlight the importance of advocacy for medical nutrition therapy for people with type 2 diabetes, with respect to alleviating the great global economic burden from this condition. Further studies are warranted to elucidate the factors that mediate and moderate cost effectiveness and to allow for the generalisation of the findings. Abstract : This scoping review aimed to map the existing literature concerning the cost effectiveness of medical nutrition therapy provided by dietitians for people with type 2 diabetes. After searching 13 scientific databases and multiple grey literature websites, four studies combining 22 765 adults with type 2 diabetes were included. Dietetic intervention was shown to be cost‐effective in terms of diabetes‐related healthcare costs and hospital charges, at the same time as also reducing the risk of absenteeism to less than half and the risk of presenteeism to less than one‐seventh.